ANALISIS METODE BALANCED SCORECARD TERHADAP PENGUKURAN KINERJA PERUSAHAAN PT.GOLDEN TEKNIK SIDOARJO TAHUN 2013 - 2015 - Aini, Putri Qurota; Sutjahyani, Dewi (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACTAssessment of the performance of the company is a company that is very important to evaluate and develop the performance. Therefore developed the concept for measuring the performance of a variety of perspectives, i.e. balanced scorecard. The purpose of this study is to measure the company's performance from the perspective of finance, customers, internal business processes, and learning and growth perspective.This research was conducted on the PT. Golden Teknik. This research was conducted using primary data from the financial statements of PT Golden Teknik, whereas data collection techniques used are literature. Results from the overall perspective of the four shows. On the financial perspective as measured by current ratio showed good results, while the debt ratio, the ratio of turnover total assets, return on assets and shows the results. On the perspective of the customer as measured by customer retention shows bad results too. In the internal business processes perspective shows good results. In the learning and growth perspective shows good results as measured by employee productivity and the level of employee training. (1). From the four perspectives of the financial perspective, i.e., to get a good result, not the perspective of a good customer, internal business process perspective is good learning and growth perspective and showed good results. The author's suggestions are therefore strongly advised to companies implementing the Balanced Scorecard performance measurement system as a company, so the company's performance is measured not only from financial performance alone, but must be measured also from non financial performance , such as performance management (2). Based on research results that PT Golden Teknik in order to continue improving innovation in developing its products, because innovation is very influential towards the survival of the company and the company's image. (3) For the next researcher is expected to examine other research on objects with a larger population numbers that will be used as the sample so that the research is more representative. (4). Companies should pay more attention to the perspective of the customer, the company shall undertake an effort to improve the company's assets to satisfy the debt by pay in (5). Management can maintain the performance of the company in order to continue to get better in the years ahead